The Impact of Flexible Workspaces on Employees’ Performance: A Bibliometric Review and Future Research Directions - Syarifa Hanoum; Muhammad Haris Jauhari; Amilia Azzahro; Ika Safitri; Uliyatun Nikmah; Mahmood Shubbak (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2024)
Purpose – This study investigates how flexible workspaces influence employee performance, assess their advantages and disadvantages, and identify untapped research potential in this evolving field, contributing to understanding of this transformative work environment. Methodology – This study employs a bibliometric approach and content analysis to analyze 104 full-text relevant documents from Scopus and Web of Science database. Findings – Flexible workspaces generally enhance employee performance by improving well-being, collaboration, autonomy, and work–life balance, particularly following COVID-19, but they may also introduce challenges such as reduced face-to-face interaction and increased distractions, thus require careful implementation in organizations. Originality – This study synthesizes studies published between 2020 and 2023 to identify dominant themes, research gaps, and future directions on the relationship between flexible workspaces and employee performance in the post-pandemic context. Research limitations – This study is limited to bibliometric and content analysis of publications from 2020–2023, a period dominated by COVID-19–driven implementations of flexible workspaces. Practical implications – Managers can optimize flexible workspace benefits through ergonomic, customizable designs and a balanced integration of open and private spaces to support focus and teamwork. Strategic use of technology and hybrid work policies further promote collaboration, minimize distractions, and reinforce organizational culture to lead sustained performance.